Handbook of Descriptive Linguistic Fieldwork - Chelliah, Shobhana L.; Reuse, Willem J. de.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
This handbook provides the most comprehensive reference on linguistic fieldwork on the market bringing together all the reader needs to carry out successful linguistic fieldwork. The book is based on the experiences of two veteran linguistic fieldworkers and advice from more than twenty active fieldwork researchers. They provide an encyclopedic review of current publications on linguistic fieldwork and offer a unique survey of past and present approaches and solutions to problems in the field. They also examine the historical, political, and social variables correlating with fieldwork in different areas of the world. The book includes information omitted in most other texts on the subject, such as the collection, representation, management, and methods of extracting grammatical information from discourse and conversational data. Extensive practical fieldwork tips are provided, as well as a handy sketch of major typological features for use in linguistic analysis.
Acknowledgements -- Chapter 1. Introduction -- Chapter 2. Definition and Goals of Descriptive Linguistic Fieldwork -- Chapter 3. The History of Linguistic Fieldwork -- Chapter 4: Choosing a Language -- Chapter 5: Field Preparation: Research, Psychological and Practical -- Chapter 6: Fieldwork Ethics: the Rights and Responsibilities of the Fieldworker -- Chapter 7: Native Speakers and Field Workers -- Chapter 8: Planning Sessions, Note Taking, and Data Management -- Chapter 9: Lexicography in Fieldwork -- Chapter 10: Phonetic and Phonological Fieldwork -- Chapter 11: Morphosyntactic Typology and Terminology -- Chapter 12: Grammar Gathering Techniques -- Chapter 13: Semantics, Pragmatics, and Text Collection -- Index.
Keywords: Linguistics; Linguistics; Linguistics, general; Electronic books